Integrasi Prinsip Keadilan Hukum Islam dalam Mengatasi Fenomena No Viral No Justice di Indonesia - Salman, Aulia; Yusuf, Andi M (Siyasah Wa Qanuniyah, 2024)
The No Viral No Justice phenomenon reflects a serious challenge in the Indonesian legal system, where the virality of a case often becomes the main factor influencing the actions of law enforcement officers, replacing the focus on evidence and facts. This condition indicates a crisis of public trust in the integrity of the law and a deviation from the principle of justice that should guarantee equality before the law. This study aims to analyze the contribution of the principles of Islamic justice in overcoming bias in law enforcement due to the influence of virality. The study was conducted using a qualitative method based on a normative theological approach, through a study of the Qur'an and Islamic legal literature. The findings show that the principles of Islamic justice, such as the principles of legality, balance, and objectivity, offer a holistic solution to correct bias in law enforcement. Islam emphasizes that justice must be upheld regardless of social status or external pressure, based on valid evidence and objective facts. The integration of Islamic justice values has the potential to strengthen the Indonesian legal system by reducing dependence on public opinion and virality. In addition, the implementation of this principle can improve the professionalism of law enforcement officers by emphasizing the importance of integrity in carrying out legal mandates. Legal reforms that include regulating social media to reduce information distortion and special training for law enforcement officers are strategic steps to achieve equal justice.